PENERAPAN TEKNOLOGI INFORMASI DAN COUSTUMER RELATIONSHIPMANAGEMENT SEBAGAI KEUNGGULAN BERSAING BERKELANJUTKANGUNA MENINGKATKAN KINERJA PERUSAHAAN - Dinata, Benny Martha; Wahyudi, Sugeng; Yuniawan, Ahyar (JURNAL BISNIS STRATEGI, 2016)
This study was conducted to examine the effect of Information Technology and Customer Relationship Management (CRM) of the Company's Performance with Sustainable Competitive Advantage as an intervening variable. Object of this research is the workshops authorized Toyota network in Central Java and Yogyakarta, Indonesia.This research is an empirical study with a sample of the entire population in the data collection. Data obtained by conducting a survey of 30 Chief and Assistant Chief Workshop an authorized Toyota network in Central Java and Yogyakarta, Indonesia. Data analysis was done using descriptive analysis and Structural Equation Model (SEM). The type of SEM in this study is the variance based SEM or Partial Least Square (PLS) SEM using an application program SmartPLS (Partial Least Square) 2.0 M3.Based on the calculation result R2 is known that variable of Information Technology, Customer Relationship Management, and Sustainable Competitive Advantage Companies able to explain the variable performance of 57.87%, while 42.13% is explained by factors outside the model. Thus, indicating that the resulting model is good and has a level of closeness that a strong correlation (substantial).